Perspectives on perioperative management of children's surgical conditions during the COVID-19 pandemic in low-income and middle-income countries: a global survey - Faye Evans; Sarah Greenberg; Fabio Botelho; Paul Truche; Alexis Bowder; David Patrick Mooney; Amber Trujillo Lalla; Robert Crum; Henry Elliot Rice; Bellisa Caldas Lopes; John Gerard Meara; Emmanuel Adoyi Ameh (BMJ Publishing Group, 2020)
Background Many organizations have issued recommendations to limit elective surgery during the coronavirus disease 2019 (COVID-19) pandemic. We surveyed providers of children's surgical care working in low-income and middle-income countries (LMICs) to understand their perspectives on surgical management in the wake of the COVID-19 pandemic and how they were subsequently modifying their surgical care practices.Methods A survey of children's surgery providers in LMICs was performed. Respondents reported how their perioperative practice had changed in response to COVID-19. They were also presented with 26 specific procedures and asked which of these procedures they were allowed to perform and which they felt they should be allowed to perform. Changes in surgical practice reported by respondents were analyzed thematically.Results A total of 132 responses were obtained from 120 unique institutions across 30 LMICs. 117/120 institutions (97.5%) had issued formal guidance on delaying or limiting elective children's surgical procedures. Facilities in LICs were less likely to have issued guidance on elective surgery compared with middle-income facilities (82% in LICs vs 99% in lower middle-income countries and 100% in upper middle-income countries, p=0.036). Although 122 (97%) providers believed cases should be limited during a global pandemic, there was no procedure where more than 61% of providers agreed cases should be delayed or canceled.Conclusions There is little consensus on which procedures should be limited or delayed among LMIC providers. Expansion of testing capacity and local, context-specific guidelines may be a better strategy than international consensus, given the disparities in availability of preoperative testing and the lack of consensus towards which procedures should be delayed.